KONSTRUKSI KARAKTER PELAJAR PANCASILA DI SMA NEGERI 1 NGEMPLAK BOYOLALI MELALUI KURIKULUM MERDEKA PADA ABAD 21 - Hendrayanto, Dhani Nur; Fitriana, Laila; SR, Agung Nugroho (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
Education plays role in shaping students who can preserve Pancasila as Indonesian characteristic. This study identifies challenges and examines the nature of best practices implemented by school through the implement of Kurikulum Merdeka to construct the Pancasila student characters in the 21st-century education era. The research method is qualitative descriptive approach with a research subjects are high school students of SMA Negeri 1 Ngemplak Boyolali. The research object is school policies in actualizing Pancasila as Indonesian characteristic. Data collected through by observations and documentations, then analyzed by data reduction, presenting results and drawing conclusion. The study results indicate challenges in the 21st-century education era related to excessive use of technologys and poorlys filtered access to information, leading to disruptions in students learning focus. The efforts made by the school involve constructing the character of students based on Pancasila values through the implement of Kurikulum Merdeka. This process carried out through by P5 activities in school, so students become accustomed. The educational approach applied by school in the 21st-century education era is student oriented, then enabling them to adapt the challenges of changing times. School have made optimaly efforts to implement the construction of Pancasila student characters in this 21st-century education era.